The Common Emotional Plot of the Four Gospels - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2019)
One way of defining or describing a plot is through its emotional structure. This article examines the emotional structure of the gospels of Matthew, Mark, Luke, and John in a modern English translation (WEB). Measures of emotion are based on quantitative sentiment analysis (Dictionary of Affect in Language). A common plot is identified for all gospels, modeled with a regression analysis (p<.001), and described in terms of the relationship of emotion to content across time. The plot opens on an emotionally positive note. Emotions become increasingly unpleasant as Jesus meets with resistance from religious authorities while engaging in his ministry. Emotions then become more pleasant as Jesus completes his pre-Judean ministry, experiences the Transfiguration, and enters Jerusalem in triumph. After this, emotions become increasingly unpleasant again, leading to the low of the crucifixion. A turn to more pleasant emotions characterizes the resurrection. In a separate analysis it was noted that segments of the gospels presented as spoken by Jesus were more pleasant than remaining materials (p<.001): however, they did not vary emotionally in accordance with the plot (p>.20), but remained relatively stable across time.